AB0453 Biological therapies retention rate in two sudamerican countries. data from biobadaguay registry. (12th June 2018) - Avila-Pedretti, M.G.; Melgarejo, P.; Franco, M.; Morel, Z.; Elizaur, J.G.; Delgadillo, P.; Acosta-Colman, I.; Cabrera, S.; Cordovilla Montero, D.; Losanto, J.; Román, L.; Paredes, E.; et al.
Abstract : Background: The retention rates (RR) of biological therapies (BT) have been extensively studied in European countries and the United States, but there is a lack of information about them in emerging populations. Objectives: To analyse BT retention rates and variables associated to them at the BIOBADAGUAY registry Methods: Patients with a chronic inflammatory arthritis enrolled in the Paraguayan-Uruguayan biological register (BIOBADAGUAY) between2015 and 2017 where included in the study. Phase I of the study was focused in the global RR analysis and association with clinical and epidemiological variables. In phase II we analysed BT retention rate according to different discontinuation motives and association with clinical and epidemiological variables. Survival analysis was performed using Kaplan-Meier estimators and proportional hazard regression models Results: A total of 778 BTs where included in the study (etanercept n=184, adalimumab n=440, rituximab n=44, infliximab n=27, tocilizumab n=75, and others n=8). The underlying diagnosis associated to these BTs were rheumatoid arthritis (RA;58.2%), juvenile arthritis (JIA; 14.2%), ankylosing spondylitis (SA; 12.5%) and psoriatic arthritis (PA; 8, 0%). In phase I we found that mean survival times were 322 (±17.9), 315 (±22.32), 289(±8.52) and 233 (±16.69) weeks for AS, PA, RA and JIA respectively. The survival association analysis has shown that JIA diagnosis (p=2.26 × 10–4, HR=1.80 [95%CI, 1.32–2.46]), corticosteroids (p=1.54 × 10–2, HR=1.38 [95% CI, 1.06–1.79]), and previous BT (p=3.32 × 10–2, HR=1.43 [95% CI, 1.03–1.98]) were variables significantly associated with a lower BT retention. In phase II, we stratified the survival analysis by cause of discontinuation. We found that corticoids (p=9.48 × 10–4 HR=2.02 [95% CI, 1.33–3.06]), female gender (p=4.36 × 10–2, HR=1.66 [95% CI, 1.01–2.72]) and previous BT (p=2.56 × 10–2, HR=1.72 [95% CI, 1.07–2.78]) were associated with lower BT retention due to inefficacy. When we analysed withdrawn according to adverse events, we found that RA (p=02, 80 × 10–2, HR=1, 83[IC 95% 1, 07–3, 15]), previous BT (p=4, 83 × 10–2, HR=1, 76[IC 95% 1, 00–3, 09]) and age (p=7, 14 × 10–5, HR=1, 05 [IC 95% 1, 02–1, 05]) were significantly associated with therapy discontinuation. In the group of treatments with discontinuation due to remission, we found that JIA diagnosis (p=7, 93 × 10–8, HR=30, 58 [IC 95% 8, 77–106, 71]), age (p=7, 83 × 10–6, HR 0, 83[IC 95% 0, 76–0, 90]) and gender (p=4, 36 × 10–2, HR 1, 66[IC 95% 1, 01–2, 72]) were associated to discontinuation due to remission. Conclusions: Our results show that different sets of clinical and demographical variables are significantly associated to biological therapy survival depending on the discontinuation cause. Disclosure of Interest: None declared